2016
DOI: 10.1007/s00436-016-4912-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of productivity of Culex spp. larvae (Diptera: Culicidae) in urban storm water catch basin system in Wrocław (SW Poland)

Abstract: In urban environments, catch basins serve as major developmental and resting sites for anthropophilic and zoophilic mosquitoes. However, the use of this habitat is inconsistent, with abundance of larvae varying significantly across catch basins at a fine spatial scale. During seasonal summer investigations on mosquito species composition, their spatial and temporal distribution and the environmental characteristic of the breeding sites in the underground storm drain systems of the Wrocław urban area (SW Poland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This finding provides new insight that Culex spp. is typically favor fresh and unpolluted water in which the water is contained inorganic ions such as Na+, Mg 2+ , Ca 2+ , Cl -NO 3-, SO4 2etc (Rydzanicz et al 2016). This study which demonstrates the dominance of Cx.…”
Section: Discussionmentioning
confidence: 56%
“…This finding provides new insight that Culex spp. is typically favor fresh and unpolluted water in which the water is contained inorganic ions such as Na+, Mg 2+ , Ca 2+ , Cl -NO 3-, SO4 2etc (Rydzanicz et al 2016). This study which demonstrates the dominance of Cx.…”
Section: Discussionmentioning
confidence: 56%
“…Stormwater infrastructure has been identified as a major source of mosquitoes in many metropolitan areas [ 19 ], especially in CBs. Rydzanicz concluded that CBs served as major development and resting sites for anthropophilic and zoophilic mosquitoes in urban Poland [ 15 ], Harbison suggested that CBs (numbers up to 200,000) are the primary source of potentially disease-carrying mosquitoes in the Chicago metropolitan area [ 19 ]. Kobayashi confirmed that catch basins were the main larval habitats in urban environments of Japan[ 20 ], and herein we have shown that this also holds true in urban Shanghai.…”
Section: Discussionmentioning
confidence: 99%
“…and Cx . torrentium was the most prevalent species in all CBs as the predominant species[ 15 ]. In China, an earlier study in Dalian located in northern China also suggested that Cx .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their design often includes a sump or vault below the outflow pipe that collects sediments and other debris, preventing this material from entering and clogging the outflow pipes. These sumps are often deep enough to permanently hold water and as a result, provide a habitat for aquatic stages of mosquito vector species, including Culex pipiens L., Culex quinquefasciatus Say, and Culex restuans Theobald (Covell and Resh 1971, Munstermann and Craig 1977, Stockwell et al 2006, Anderson et al 2011, Rydzanicz et al 2016, Cx. quinquefasciatus (Say) (Maddock et al 1963, Rey et al 2006, Molaei et al 2007, Aedes albopictus (Skuse) (Prioteasa et al 2015, Vallorani et al 2015 and Ae.…”
Section: Introductionmentioning
confidence: 99%